2019
DOI: 10.1038/s41598-019-52775-5
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic adaptations mediate the effect of hydration on brain functioning and mood: Evidence from two randomized controlled trials

Abstract: Dehydration (water loss >2.0% of body weight) has significant negative effects on physical and mental performance. In two studies the effects of minor hypo-hydration (water loss <1.0% of body weight) on CNS function, mood and cardiovascular functioning were measured. Study 1: On two mornings twelve male participants were exposed to a temperature of 30 °C for four hours and either did or did not drink two 150 ml glasses of water during that time. Study 2: Fifty-six (25 M) individuals were exposed to the same 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
0
20
0
2
Order By: Relevance
“…Lacking access to water while in a mildly dehydrated condition increases anxiety and can change decision-making practices (H. A. Young et al, 2019 ), which may increase transmission risk of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Lacking access to water while in a mildly dehydrated condition increases anxiety and can change decision-making practices (H. A. Young et al, 2019 ), which may increase transmission risk of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, HR variability (HRV) is considered a practical way of assessing ANS in many situations. HRV evaluates the oscillations between inter-beat cardiac intervals (IBI) and scrutinizes the control of the ANS over heart rhythm (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Goncharova et al reported that AVP receptor 1b antagonist injection reduced ACTH secretion in response to insulin-induced hypoglycaemia in female primates apparently experiencing increased anxiety, as indicated by increased motor activity (38) . One recent human study also examined thirst and mood with mild hypohydration induced by water restriction and heat and suggested that autonomous nervous system activity, measured with fMRI, may have negative consequences for mood (17) . Copeptin, as a surrogate marker of vasopressin, has been studied for its potential role in various health issues (39) and its interaction with CRH (40) .…”
Section: Discussionmentioning
confidence: 99%
“…When these responses are not able to restore uncompensated water losses, dehydration can occur and induce disturbances to cognition and mood. Specifically, recent studies have reported that cognitive function and mood are impaired when mild dehydration (<2 % reduction in body weight) is present (7,8,(15)(16)(17)(18) as well as by water deprivation for 24 h or more (19)(20)(21) . However, common methods for inducing dehydration (i.e.…”
mentioning
confidence: 99%